Amine-based Carbon Dioxide Absorption: The Ionic Strength Effect on the Monoethanolamine Protonation Constant at Temperatures from 313 to 333K - Sholeh Ma'mun; Panji Kumala Setiawan; Egip Indrayanto (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
Amine-based absorption has been extensively used for carbon dioxide (CO2) removal processes, such as CO2 absorption from flue gas as well as from natural gas. As a reactive system in which the chemical reaction, as well as mass transfer, occur simultaneously, an experimental determination of equilibrium reaction constants, e.g. acid dissociation/protonation constant (Ka), is, therefore, necessary to be conducted. This study aims to evaluate the ionic strength effect from 0.06 to 6.0 m (mol/kg water) on the Ka value of monoethanolamine (MEA) at temperatures between 313 and 333K. The experimental results indicate that the pKa values tend to be increasing as the ionic strength increases. This is contradicting to the temperature effect where the pKa values tend to be decreasing as the temperature increases. Furthermore, the extended Debye-Hückel formulation was implemented to predict the species activity coefficients.